2018
DOI: 10.32861/jssr.spi6.825.831
|View full text |Cite
|
Sign up to set email alerts
|

Vocational Education Principal of Leadership: A Case Study in East Nusa Tenggara

Abstract: Malaysia is estimated to become an "aging society" country by 2030 due to the increase in the number of senior citizens in the country. This is expected to lead to issues relevant to the welfare of the elderly when there is an outflow of guardians to the urban cities. Thus, this study was conducted to explain the pattern of caring for the elderly among their guardians. This qualitative study was conducted in Yan, Kedah, involving 26 respondents among the elderly. Face-to-face interviews have been conducted by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The study results showed a relationship between the birth length of toddlers, history of exclusive breastfeeding, family income, mother's education, and maternal nutrition knowledge on the incidence of stunting in toddlers. Therefore, integrated and multisectoral programs are needed to increase family income, education, nutrition knowledge, and exclusive breastfeeding in reducing stunting [11][12][13][14][15][16][17]. low family economic status is a significant risk factor for stunting in toddlers aged 2-3 years [4,15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study results showed a relationship between the birth length of toddlers, history of exclusive breastfeeding, family income, mother's education, and maternal nutrition knowledge on the incidence of stunting in toddlers. Therefore, integrated and multisectoral programs are needed to increase family income, education, nutrition knowledge, and exclusive breastfeeding in reducing stunting [11][12][13][14][15][16][17]. low family economic status is a significant risk factor for stunting in toddlers aged 2-3 years [4,15].…”
Section: Discussionmentioning
confidence: 99%
“…One of the efforts to prevent and treat stunting is to carry out specific nutrition interventions and sensitive nutrition interventions on the target of the first 1,000 days of a child's life up to the age of 6 years [6,15,17]. This intervention requires continuous supervision and assistance and continuous and scheduled monitoring.…”
Section: The Effectiveness Of Ipc On the Attitude Of Health Cadres On Stuntingmentioning
confidence: 99%
See 1 more Smart Citation
“…Transactional leadership in this study is a leadership model in the food and beverage industry in Surakarta City that guides, motivates, and supervises employees to achieve the goals set and rewards performance. Leaders know employees' wishes, leaders exchange employees' efforts in return, the leader is responsive to the employee's self management by exception, passive management (Jumintono et al, 2018). Job satisfaction is an emotional state of employees of the food and beverage industry that is pleasant or unpleasant caused by evaluating the job and work situation financial compensation and transactional leadership are studies that must be conducted to analyze their effect on employee performance.…”
Section: Conceptualization and Hypothesesmentioning
confidence: 99%
“…Video learning can increase student knowledge [3]. Strengthening school education is understanding benchmarking, professional training, and increasing trust, strong character with high integrity [4].…”
Section: Introductionmentioning
confidence: 99%